2020
DOI: 10.3390/ijms21239153
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial Calcium Homeostasis in Alzheimer’s and Related Diseases

Abstract: Calcium signaling is essential for neuronal function, and its dysregulation has been implicated across neurodegenerative diseases, including Alzheimer’s disease (AD). A close reciprocal relationship exists between calcium signaling and mitochondrial function. Growing evidence in a variety of AD models indicates that calcium dyshomeostasis drastically alters mitochondrial activity which, in turn, drives neurodegeneration. This review discusses the potential pathogenic mechanisms by which calcium impairs mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 158 publications
(198 reference statements)
2
40
0
Order By: Relevance
“…Many aspects of mitochondrial dysfunction have been observed in neurodegenerative conditions: change in their size and number, abnormal mitochondrial dynamics, reduced energy metabolism, reduced expression and activity of key enzymes of oxidative metabolism, increased rate of mutations in mitochondrial DNA (mtDNA), increased vulnerability to ROS attack and activation of intrinsic apoptotic pathway components (although not necessarily leading to apoptosis) [7,21,34,35]. OS-induced endoplasmic reticulum (ER) stress, calcium overload and disturbance of mitochondrial calcium homeostasis further contribute to mitochondrial failure and disease progression [7,[36][37][38].…”
Section: Oxidative Stress In Neurodegenerative Diseases: the Role Of Nrf2 Pathwaymentioning
confidence: 99%
“…Many aspects of mitochondrial dysfunction have been observed in neurodegenerative conditions: change in their size and number, abnormal mitochondrial dynamics, reduced energy metabolism, reduced expression and activity of key enzymes of oxidative metabolism, increased rate of mutations in mitochondrial DNA (mtDNA), increased vulnerability to ROS attack and activation of intrinsic apoptotic pathway components (although not necessarily leading to apoptosis) [7,21,34,35]. OS-induced endoplasmic reticulum (ER) stress, calcium overload and disturbance of mitochondrial calcium homeostasis further contribute to mitochondrial failure and disease progression [7,[36][37][38].…”
Section: Oxidative Stress In Neurodegenerative Diseases: the Role Of Nrf2 Pathwaymentioning
confidence: 99%
“…Indeed, this is an effect of exogenous Aβ peptides that has been experimentally demonstrated [ 150 , 151 ]. Cumulative lines of evidence have demonstrated that mitochondrial Ca 2+ signaling is altered in AD due to mutations in the PSEN proteins [ 152 , 153 ]. The excess in cytosolic Ca 2+ caused by enhanced ER Ca 2+ release caused by mutant PSENs is, at least in part, counterbalanced by the Ca 2+ uptake through the voltage-dependent anion-selective channel protein and the calcium uniporter of the mitochondria.…”
Section: Modulation By Aβ Of Cambps Which Play Major Roles In Aβ Production In Neuronal Calcium Homeostasis and Ltpmentioning
confidence: 99%
“…A sustained increase in mitochondrial Ca 2+ concentration impairs ATP production, increases reactive oxygen species (ROS) production, and the opening of the mitochondrial permeability transition pore [ 154 ]. Several studies have proposed that enhanced neuronal apoptosis and increased ROS production are major factors in the neurodegeneration observed in AD, and the accumulation of mitochondrial Ca 2+ has been shown to be significantly implicated in these neurotoxic pathways [ 153 , 154 ]. Upregulation of genes related to mitochondrial energy metabolism and apoptosis has been already reported in an AD transgenic mouse model overexpressing a mutant form of APP at different stages of AD progression [ 155 ].…”
Section: Modulation By Aβ Of Cambps Which Play Major Roles In Aβ Production In Neuronal Calcium Homeostasis and Ltpmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the multifactorial aspect of AD, it is more likely that pleiotropic mechanisms interfere with each other or exist side by side, finally leading to pathological changes. For example, Aβ has been shown in cell culture and animal models to enhance cytoplasmic calcium levels, and elevated calcium, in turn, interferes with mitochondrial function, reducing ATP production [14][15][16][17]. Decreased energy or ATP level are a common characteristic of AD [18,19].…”
Section: Introductionmentioning
confidence: 99%